Reciprocal Data Portability to Foster Financial Services Competition in the Open Banking System Era - Wiwoho, Jamal; Pati, Umi Khaerah; Pratama, Anugrah Muhtarom (Faculty of Law, Universitas Sebelas Maret, 2024)
This article analyzes the feasibility of incorporating reciprocal financial data into Indonesia's open banking system by studying its implementation in the United Kingdom and other countries. The methodology employed is conceptual, statutory, and comparative legal, utilizing data gathered from secondary legal sources. The study discovered that reciprocal data finance could be a supplementary measure to enhance data portability rights. This approach enables banks to provide compensation for access to account data, utilizing the concept of